The Double-Edged Sword: How Women's Financial Inclusion Affects Intimate Partner Violence in India - Shreemoyee Shreemoyee; Punarjit Roychowdhury; Gaurav Dhamija (Global Labor Organization (GLO), 2025)
We empirically examine the causal impact of women's financial inclusion on their exposure to Intimate Partner Violence (IPV) in India using data from the fifth round of the National Family Health Survey. However, establishing a causal link between women's financial inclusion and IPV is challenging due to unobserved confounders and reverse causality. To overcome these obstacles, we adopt a nonparametric bounds approach. We find robust evidence that women's financial inclusion significantly increases their exposure to IPV by at least 7.8 percentage points. We provide suggestive evidence that this result arises because women's financial inclusion is likely to disrupt patriarchal beliefs about gender roles, lead to female guilt, and increase husbands' use of IPV for instrumental reasons. Our findings suggest that empowering women financially, while crucial, may inadvertently increase their vulnerability to IPV unless such initiatives are paired with efforts to shift underlying cultural norms surrounding gender.
Keywords: J12; J16; O12; 330; Intimate Partner Violence; Financial Inclusion; Partial Identification; India